STUDIES ON QUALITATIVE AND QUANTITATIVE PHYTOCHEMICAL ANALYSIS OF PIPER LONGUM LINN. - ESHA RAMI,; SAFURA SIPAI,; ILLA PATEL, (International Journal of Pharma and Bio Sciences, 2013)
The present study aimed to carried out a qualitative and quantitative analysis of Piper longum. Various extract of different plant parts of piper longum revealed the presence of various important bioactive compounds viz. alkaloid, flavonoids, glycosides, tannin, phenol and sterol. Quantitative analysis showed highest amount of phenol content (24. 27 mg GAE/ gm) in leaf and total flavonoids content (3.27 mg quercetin/gm) content in root in Methanolic extract.